Tradução comentada da cartilha Violência sexual contra crianças e adolescentes de língua portuguesa para Libras - Silva, Rhuan Lucas Braz (2022)
This work belongs to Translation Studies and Community Interpreting area, also known as translation and interpretation of public services. In this sense, translation from/to/between sign languages offers important contributions to expanding the linguistic rights of deaf people, especially in terms of access to information. With regard to deaf children and adolescents, materials translated into Libras are not always available and/or are the target of interest of governmental policies. Sign languages must be guaranteed as a right of deaf people, and must be recognized in different social contexts, whether legal, educational, medical-hospital, familiar and others. In this way, thinking about translation aimed at this audience is a way of guaranteeing that their rights are accessed and enjoyed. This way, the general objective of this work was to analyze the linguistic, translational and cultural challenges of the annotated translation process of the booklet “SViolência Sexual Contra Crianças e Adolescentes – O Silêncio que Destrói Infâncias” into Brazilian Sign Language. Based on the theoretical contributions of Phillipson and Skutnabb (1995), Pöchhacker (2004), Hale (2007), Abreu (2018), Rodrigues and Beer (2016) and Rodrigues and Santos (2018), the need to broaden discussions on the relevance and role of translation from/to/between sign languages in public contexts, considering the scope and different Brazilian deaf communities. We used the case study methodology, developing a commented translation. The construction of the translation project followed the functionalist guidelines developed by Nord (2016). Finally, the translation itself is carried out and then comments are made on the main highlights and the decisions taken in the translation process with regard to general aspects of the theme, the booklet, the textual genre and the linguistic aspects.